Jointly acquired and heritage property in the context of FELDA’s new model strategy: A family heritage innovation plan - Urus, Nur Sarah Tajul; Yusoff, Mus’ab; Salleh, Maffuza; Serji, Rabi’ah Muhammad; Yusof, Naziree Mohd (Linguistics and Culture Review, 2021)
The Federal Land Development Authority (FELDA) began its innovative concept when FELDA’s New Model Strategy which went through the evolutionary process in its distinctive niche was first launched in 2020. The New Model Strategy has a significant impact on the efforts to determine FELDA’s vision and direction in changing the mentality of the settlers and rejuvenating FELDA thus driving the aspect of the integrated use of modern technology, mechanisation, automation and intelligent agriculture. Besides, the implementation of the diversity of crops on farms such as pineapple, young ginger, black turmeric and herbs. FELDA is a Malaysian government agency that addresses the relocation of poor rural people to newly developed areas to improve their economic status. FELDA’s original main focus was the opening of smallholder farms for contemporary crops. FELDA settlers’ husband works hand-in-hand in sustaining FELDA’s aspiration to increase daily household income. Typically, conflicts appear when the death or divorce of FELDA settlers occurs and their wives or heirs made property claims. FELDA land issues were discussed based on the types of land titles in the National Land Code 1965 and legal restrictions in Section 14(2) of the Group Land Act 1960.